(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: To evaluate results of treatment pneumonia for children aged 2 months to 5 years in pediatric deapartment at Yen Phong health center, Bac Ninh. Subjects: Patients with pneumonia aged 2 months to 5 years for treatment from September 2020 to June 2021. Methods: Descriptive study. Results: A total of 146 children were diagnosed with pneumonia, of which 82 were male (56.3%). The mean age was 20.6 ± 14.2 months. Prevalence of antibiotic use in the pre-hospital was 69.9%. The most common clinical manifestations were cough (100.0%), a subcrepitant rales (100.0%) and fever (29.5%). The most common X-ray was widespread patchy infiltrates (61.0%). 77.4% of children used combination antibiotics, in which the most common combination was Cephalosporin + Aminoglycoside (67.8%). Average duration of treatment was 6,7 ± 2,2 days. The cure rate was 100%. Conclusion: Pneumonia is more common in children less than 1 year old, with clinical manifestations of cough, shortness of breath and a subcrepitant rales. Combination antibiotics are effective in treating pneumonia in young children.